Application of a new instrument to measure injuries and disability at the Iganga-Mayuge demographic surveillance system (im-dss), Uganda. (7th October 2012) - Bachani, AM; Hyder, AA; Kadobera, D; Galiwango, E; Rutebemberwa, E; Bishai, D; Wegener, S; Morrow, RH
Abstract : Background: Millions of injured individuals survive worldwide each year, often with life-long disabilities. However, the measurement of post-injury outcomes, especially in low-income settings remains a major deficiency in health information systems. Aims/Objective/Purpose: We apply a new short, 8-question instrument to screen for injuries and disabilities at the IM-DSS in Uganda. Methods: We utilised a modified version of the short set of questions proposed by the Washington Group on Disability Statistics. Information on injuries sustained within the prior year, and activity limitations was collected on all individuals over the age of 5 who were residents of the IM-DSS. Results/Outcomes: 57 247 individuals were included in the survey. 596 individuals reported having had an injury (62% Male; 38% Female). Of these, the majority were Road Traffic Injuries (41%), followed by falls, blunt injuries, and burns. Individuals between the ages of 15–59 years accounted for more than half of all injuries. 82% of injured persons also reported having a disability (OR 61; 95% CI 47.9 to 77.7; p<0.001). The most common types of difficulties reported were vision and mobility (lower and upper mobility). Significance/Contribution to the Field: This study shows that the modified short set of questions can be readily applied to obtain estimates on the prevalence and types of post-injury disability at the population level—a step towards understanding the long-term consequences of injuries and the type of care needed to address them in the population. This instrument could be adapted for use in other such settings allowing for comparable estimates across different regions and populations.